2011
DOI: 10.1152/ajpgi.00239.2011
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of gut commensal bacteria attenuates intestinal ischemia/reperfusion injury

Abstract: Gut commensal bacteria play important roles in the development and homeostasis of intestinal immunity. However, the role of gut commensals in intestinal ischemia/reperfusion (I/R) injury is unclear. To determine the roles of gut commensal bacteria in intestinal IR injury, we depleted gut microbiota with a broad-spectrum antibiotic cocktail and performed mesenteric I/R (M I/R). First, we confirmed that antibiotic treatment completely depleted gut commensal bacteria and diminished the size of secondary lymphoid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
97
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 99 publications
(103 citation statements)
references
References 73 publications
(103 reference statements)
4
97
1
1
Order By: Relevance
“…Mucosal antibodies have the potential to recognize "neoantigens" revealed on ischemic cells and to activate the complement pathway, leading to exacerbate damage during I/R-induced injury. 10,30,39,40 Increased intestinal IgA and IgM deposition after I/R injury in mice was previously reported. 10 Because Myd88 IEC−/− mice have lower basal levels of luminal IgA, we hypothesized that these mice would display diminished deposition of IgA in injured tissue.…”
Section: Discussionmentioning
confidence: 54%
See 4 more Smart Citations
“…Mucosal antibodies have the potential to recognize "neoantigens" revealed on ischemic cells and to activate the complement pathway, leading to exacerbate damage during I/R-induced injury. 10,30,39,40 Increased intestinal IgA and IgM deposition after I/R injury in mice was previously reported. 10 Because Myd88 IEC−/− mice have lower basal levels of luminal IgA, we hypothesized that these mice would display diminished deposition of IgA in injured tissue.…”
Section: Discussionmentioning
confidence: 54%
“…10,30,39,40 Increased intestinal IgA and IgM deposition after I/R injury in mice was previously reported. 10 Because Myd88 IEC−/− mice have lower basal levels of luminal IgA, we hypothesized that these mice would display diminished deposition of IgA in injured tissue. We focused on IgA because a previous study reported similar levels of IgG and IgM but lower IgA levels in Myd88 −/− mice compared with wild-type mice.…”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations